DKI Jakarta’s Odd-Even Transportation Policy Formulation from The Perspective of Evidence Based Policy - Eko Prasojo; Afwan Abdi Salam (Policy & Governance Review, 2022)
This research describes the policy formulation of the odd-even traffic restriction system in DKI Jakarta from the perspective of an evidence- based policy. The odd-even policy seeks to solve congestion and environmental problems due to using private vehicles that have not been fully resolved. The researchers used the concept of evidence-based policy (Head, 2008) to understand three dimensions of evidence, namely political knowledge, scientific (research-based) knowledge, and practical implementation knowledge. The researchers used the post-positivist paradigm in this study to obtain a holistic analysis and to understand the possibility of other variables not discussed in previous theories through in-depth interviews and literature studies. The results show there was stakeholder involvement in the systemic-participatory process limited to NGOs and academics. Meanwhile, business interest groups were reactively involved through mass media support. The Transportation Department of DKI Jakarta had used data and information in the traffic restriction policy formulation with the odd-even system. Limitations in data resulted in the inability to provide a holistic picture related to traffic conditions and the effects of the odd-even policy implementation in DKI Jakarta. Practically, the odd-even policy formulation had shaped the preparedness of the implementing instruments in the odd-even policy implementation. Meanwhile, theoretically, this study found two determinant factors in the formation of political knowledge not stated by Head (2008), namely legal certainty and mass media role.